The Effect of PNMDigi Applications, Prices, and Advertising on Customer Loyalty and Customer Satisfaction as Intervening Variables at PT. Permodalan Nasional Madani - Suntari; Sri Wahyuni (International Journal of Asian Business and Management, 2023)
This study aims to examine the effect of the PNMDigi application, price, advertising on customer loyalty at PT. Civil National Capital with customer satisfaction as a modifying factor. The PLS program is used in this study's quantitative method of structural equation modeling (SEM). IBM Statistics SPSS 26.0, as well. The customer of PT. Permodalan Nasional Madani serves as the analytical unit. There were 125 responders for the sample. A questionnaire that was sent online was used as the data gathering method. The findings demonstrated that customer satisfaction can operate as a mediator between the PNMDigi application's effect on customer loyalty. at PT. Permodalan Nasional Madani